Developing non-cognitive skills in part-time students at a South African university: Overcoming negativity and supporting behavioural change - Merino, A.; Jooste, S.; Vermeulen, K. (South African Journal of Higher Education, 2020)
This paper reports on the findings of an intervention aimed at assisting a group of thirty-one part-time students registered for a third year Management Accounting and Finance course to develop a range of non-cognitive skills that have been shown to positively impact academic behaviour. In addition to facilitating the teaching and learning of academic content, lecturers introduced students to academic mindsets, academic behaviours, learning strategies and social skills through role-plays and practical demonstrations. The intervention also strove to influence the context in which students learned in order to positively influence the attitudes of the students towards the course and to motivate them to acquire and practice behaviours that would support their learning. The intervention involved two action research cycles in which the researchers were able to reflect on the effectiveness of the various approaches used to encourage behaviour change and the acquisition of new skills. The findings of the study indicate that the intervention was successful in developing a range of non-cognitive attitudes, strategies and behaviours in students, with most of the cohort reporting positive changes in attitude towards their studies and the belief that academic success was indeed possible.